PERSEPSI MAHASISWA EKONOMI SYARIAH STAI DDI PINRANG TENTANG NISBAH DAN BUNGA BANK (Implikasinya terhadap Pemahaman Ekonomi Syariah) - Lina Lina; Mardia Mardia; Rasyidah Bulqis (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstrak. This research discusses about Nisbah and bank interest is a system applied in Islamic banks and conventional banks, where Islamic banks apply an operational system with a ratio or profit sharing and conventional banks apply a bank interest operational system. This study aims to determine the perceptions of Islamic economics students, especially STAI DDI Pinrang students about the ratio and bank interest. This research uses a qualitative approach and in collecting primary data using observation, interview and documentation methods. The data analysis technique is data reduction, data presentation and conclusion drawing. The results of the study showed that: 1) The perception of STAI DDI Pinrang sharia economics students about nisbah (profit sharing) shows a positive thing. This is because students accept the presence of Islamic banks whose operational system uses a ratio or profit sharing which is an alternative to avoid usury. The perception of STAI DDI Pinrang Islamic economics students about bank interest shows a negative thing. This is because STAI DDI Pinrang Islamic economics students know bank interest is very burdensome for customers. 2) The results showed that the factors that influence the perception of Islamic economics students of STAI DDI Pinrang about the ratio and bank interest are the factors that influence students to choose Islamic banks are economic factors and non-economic factors while the factors that influence students to choose conventional banks are convenience in terms of transactions, better known and the lack of understanding of students about Islamic banks.This is evidenced by the ten people that researchers interviewed six people who use Islamic banks and four others who use conventional banks. Keywords: Nisbah (Profit Sharing), Bank Interest Abstrak. Penelitian ini membahas tentang Nisbah dan Bunga bank adalah sistem yang diterapkan di bank bank syariah dan bank konvensional, Dimana bank syariah menerapkan sistem operasional dengan nisbah atau bagi hasil dan bank konvensional menerapkan sistem operasional bunga bank. Penelitian ini bertujuan untuk mengetahui persepsi mahasiswa ekonomi syariah khususnya mahasiswa STAI DDI Pinrang tentang nisbah dan bunga bank. Penelitian ini menggunakan pendekatan kualitatif dan dalam mengumpulkan data primer menggunakan metode observasi, wawancara dan dokumentasi. Adapun Teknik analisis datanya yaitu reduksi data, penyajian data dan penarikan kesimpulan. Hasil kajian menunjukkan bahwa: 1) Persepsi mahasiswa ekonomi syariah STAI DDI Pinrang tentang nisbah (bagi hasil) menunjukkan hal yang positif. Hal ini dikarenakan mahasiswa menerima akan hadirnya bank syariah yang sistem operasionalnya menggunakan nisbah atau bagi hasil yang menjadi alternatif untuk menghindari riba. Adapun persepsi mahasiswa ekonomi syariah STAI DDI Pinrang tentang bunga bank menunjukkan hal yang negatif. Hal ini dikarenakan mahasiswa ekonomi syariah STAI DDI Pinrang mengetahui bunga bank sangat memberatkan nasabah. 2) Faktor yang mempengaruhi mahasiswa memilih bank syariah adalah faktor ekonomi dan faktor non ekonomi sedangkan faktor yang mempengaruhi mahasiswa memilih bank konvensional adalah kemudahan dalam hal transaksi, lebih dulunya dikenal dan minimnya pemahaman mahasiswa tentang bank syariah. Hal ini dibuktikan dengan sepuluh orang yang peneliti wawancarai enam orang yang menggunakan bank syariah dan empat lainnya yang menggunakan bank konvensional. Kata Kunci: Nisbah (Bagi hasil), Bunga bank